A randomised control trial for the restoration of functional ability in patients post total knee arthroplasty: a comparison of eccentric versus concentric cycling ergometry - Bakkum, Amanda (MRC/UCT RU for Exercise and Sport Medicine, 2016)
Includes bibliographical references